Mechanism of activation of the mouse c-mos oncogene by the LTR of an intracisternal A-particle gene. - Horowitz, M (1984)
In the mouse myeloma XRPC-24 the DNA of an intracisternal A-particle (IAP) is inserted within the coding region of c-mos. This insertion splits the c-mos into a 3' rc-mos and a 5' rc-mos separated by approximately 4.7 kb of IAP DNA. The insertion is in a head-to-head orientation and brings the 5' LTR of the IAP in juxtaposition to the 3' rc-mos such that the IAP and the 3' rc-mos are transcribed in opposite directions. The intact c-mos gene is usually dormant, whereas the 3' rc-mos is actively transcribed and is capable of transforming NIH3T3 cells. In an effort to understand the nature of this activation we mapped the 5' ends of the 3' rc-mos mRNA present in XPRC-24. We found two main mRNA start sites, one mapping to the junction of the 3' rc-mos and the 5' LTR, and the other located 10 nucleotides upstream to this junction, within the 5' LTR. This result indicates that the 3' rc-mos in XRPC-24 was activated by insertion of a promoter provided by the LTR of an IAP genome. Furthermore, the 5' LTR appears to possess promoter activities in two directions. This conclusion was confirmed by the fact that this 5' LTR, in both orientations, was able to activate the bacterial gene coding for chloramphenicol acetyltransferase (CAT) in the modular vector pSVOCAT.